C-6c=0

Simple and best practice solution for C-6c=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for C-6c=0 equation:


Simplifying
C + -6c = 0

Solving
C + -6c = 0

Solving for variable 'C'.

Move all terms containing C to the left, all other terms to the right.

Add '6c' to each side of the equation.
C + -6c + 6c = 0 + 6c

Combine like terms: -6c + 6c = 0
C + 0 = 0 + 6c
C = 0 + 6c
Remove the zero:
C = 6c

Simplifying
C = 6c

See similar equations:

| (11r+6)(5r-4)=0 | | Y=0.6(100)+b | | 6n^2/2 | | x+13=5x | | 5(x)=5(2x-3) | | R=b^2+1 | | (5x)2=15x-45 | | 3c-1=c | | 3x-5-x=2x-3 | | 3ysquared= | | 3(2x+1)-2(3-2)=13 | | 15x-45/2=5x | | 1/3x3/8 | | (7a)x(2b)=0 | | 15/105 | | 9z+4-5z-5= | | -6(r-7)=-54 | | 8+9a=7 | | 4x+3+2y=11 | | 7x-4.23=0.2+2.57 | | 7x-4.23=0.2 | | -8(n-2)-2=-21-3n | | 3x=2(7x-3) | | 80+5x=7x | | 4(5r-5)=-20-7r | | -5=7-2x | | (3x-1)(x+2)=-1 | | -x-3(-5x-8)=136 | | (12^5)/(9^2)*(4^4) | | 12^5/9^2*4^4 | | 0.3x-2(0.1x+0.4)= | | (3a-9)/(3a-6)*(a/a^2-9) |

Equations solver categories